KUALITAS INFORMASI DAN KEAMANAN TRANSAKSI FAKTOR KUNCI PENUNJANG PERKEMBANGAN E-COMMERCE - Resa, Asep Lucky; Wibowo, Lili Adi (Universitas Pendidikan Indonesia, 2016)
Purpose - The purpose of this paper was to be found out the influence factors of the dominant country of origin against purchasing decisions on local brandDesign/methodology/approach – the design of the research was a cross-sectional design. This research used verification approach with survey method. A total of 200 respondents were chosen as using non probability sampling. A survey questionnaire was used as a research instrument to collect the data from respondents. The analysis technique used SEM analysis tools'Findings - Quality of information and transaction security has influenced on purchase decisions online simultaneously and partially.Originality/value - The paper provides a basis to understand the issues of purchasing decisions on local brand in Indonesia. The difference of this study with earlier research on objects that are the variable used supporting the theory as well as the different references used by previous researchers. Keywords: country of origin, purchase decisions